Some engineering properties of natural building cut stones of Cyprus - Eren, Özgür; Bahali, Mustafa (Elsevier, 2005)
Natural building cut (NBC) stones are being used in Cyprus for ages to build masonry structures because of being abundant, relatively easy to cut and shape and good performance in many applications. Almost all of the historical buildings in Cyprus are made of these NBC stones. Although these stones are low cost construction materials, they are not widely used in these days. This is due to lack of knowledge causing incorrect construction methods and highly skilled labour requirement. For this study two quarries are selected and samples obtained were tested for some physical and mechanical properties. Traditional names of these NBC stones are Meluşa Stone and Karpaz Stone (or Bouri Stone). The physical properties such as bulk density, water absorption, specific gravity and porosity were measured. The mechanical properties such as compressive strength, flexural strength, direct tensile strength, splitting tensile strength, point load strength, fire resistance, abrasion resistance and freeze-thaw resistance were measured. From the results obtained it can be said that Meluşa stone behaved better than Karpaz stone. A regression analysis also provided a polynomial relation between compressive strength and burning temperature and flexural strength and burning temperature.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/j.conbuildmat.2004.05.011) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Natural building cut stone; Fire resistance; Strength; Abrasion; Freeze-thaw resistance